Physicochemical Changes in Gluten Following Oxalic Acid–Induced Deamidation: FTIR, HPLC, and Solubility Analysis - Kardian Rinaldi; Nancy Siti Djenar; Gina Almalia Rahma; Vallen Zulaikha Setiansyah Trisna (Akta Kimia Indonesia, 2026)
Gluten, a wheat-derived plant protein used in bread-making, animal protein replacement, and biodegradable packaging, suffers from water insolubility and allergenicity. Deamidation using oxalic acid addresses these limitations. Gluten was deamidated with 0.034, 0.082, and 0.133 M oxalic acid at 80°C for 30 minutes, followed by neutralization, dialysis, and freeze-drying. Physicochemical properties were evaluated using fourier-transform infrared (FTIR) spectroscopy, high-performance liquid chromatography (HPLC), and solubility tests. FTIR analysis showed the primary structure remained intact (amide I at 1580–1659 cm⁻¹; amide II at 1500–1600 cm⁻¹; amide III at 1200–1400 cm⁻¹). Secondary structure analysis revealed concentration-dependent changes in peak intensity: 0.034 M increased β-turn intensity (1665–1689 cm⁻¹), while 0.082 M and 0.133 M decreased α-helix (1580–1659 cm⁻¹) and β-sheet (1612–1643 cm⁻¹) intensities, indicating successful deamidation. HPLC analysis confirmed asparagine conversion to aspartic acid (from 8,406.54 to 464,537.33 mg/kg) and increased essential amino acids (valine, methionine, phenylalanine, isoleucine, leucine, lysine). Glutamic acid and cystine were undetected, consistent with FTIR-observed β-sheet reduction due to disulfide bond cleavage. Solubility improved markedly at 0.082 M and 0.133 M, correlating with reduced ordered secondary structures and increased polar amino acids. Oxalic acid-mediated deamidation enhances gluten solubility and nutritional profile while preserving structural integrity, with FTIR and HPLC providing complementary evidence of deamidation success. Deamidated gluten shows promise as a functional ingredient for food applications requiring improved solubility and nutrition.